DANUBE TOURIST SHIPS AS AN OPPORTUNITY FOR EXPORT OF AGRICULTURAL AND FOOD PRODUCTS - Tešanović, Dragan; Vuksanović, Nikola; Kalenjuk, Bojana; Vukić, Milorad; Gagić, Snježana (Economics of Agriculture, 2013)
The Danube is the most important European river that forms part of the trans-European navigation system Rheine – Main - Danube, which facilitates an intensive development of various forms of tourism. Currently we are experiencing the intense development of nautical tourism. Number of cruise ships and tourists is constantly increasing. The highest level of consumption while cruising is achieved on the ship itself. Countries that have not adapted well and developed the infrastructure needed for providing the material goods for the ships needs experience reduced tourist revenues. They mostly come from souvenirs and visits to cultural and historic resources. Supplies of fuel, water, food, drinks and other necessities are obtained in countries that have recognized the demand and quickly adapted its offer. Of all countries along the Danube, ours is the only one where no procuring is taking place. The purpose of this paper is to study the structure, market forms and quantities of vegetables, fruit and other foods and food products, which are yearly spent on ships analysed. This paper will point out the places and countries they are presently purchasing. The study involved six cruise ships of Grand Circle Corporation and the consumption they had during the 2011. The obtained data is systematized and presented in appropriate tables and graphs.